Parents' perspectives on a collaborative approach to the application of the Handwriting Without Tears® programme with children with Down syndrome. (13th July 2016) - Patton, Sandra; Hutton, Eve
Abstract : Background: The active involvement of parents and children in goal setting and intervention is integral to contemporary occupational therapy process models. However, parental perspectives on collaborative handwriting intervention are limited. This paper presents parental perspectives on a three‐way collaboration involving teachers, parents and an occupational therapist in the application of Handwriting Without Tears ® (HWT ® ) with children with Down syndrome. Methods: Within a larger mixed methods study, 44 parents completed purpose‐designed questionnaires and six parents participated in a focus group, post 8 months of programme implementation. Both methods gathered parent's perspectives on the usefulness and limitations of applying HWT ® . The focus group explored collaboration in depth. Analysis involved triangulation of data from descriptive analysis of numerical data with content analysis of open‐ended questions and focus group data. Findings: Enablers of parent–child engagement in HWT ® were identified as; the parent–child‐friendly aspects of HWT ®, the teacher involvement ensuring continuity which eased demands on parents, the ongoing support/guidance of the occupational therapist and the child's involvement in HWT ® group intervention. The occupational therapists' involvement was reported as essential to encouraging teacher/parent involvement. Barriers to child–parent engagement included fluctuations in child health, mood, attention span and time limitations including the child's involvement in other therapy programmes. Conclusions: Parents perceived the HWT ® and the three‐way collaborative approach as enabling active parent–child engagement in handwriting intervention. This approach warrants further investigation. Findings have the potential to inform practice guidelines and pre‐ and post‐graduation education related to collaborative handwriting intervention with children with Down syndrome and their families.